HAMBATAN EPISTEMOLOGI PEMAHAMAN KONSEPTUAL BERDASARKAN TAKSONOMI SOLO SISWA - Zhafirah Atiqah Utami; Sugiatno Sugiatno; Romal Ijuddin (UNIVERSITAS TANJUNGPURA, 2020)
This study aims to explain and describe the epistemological obstacle of students' mathematical conceptual understanding based on the SOLO taxonomy at MTs Negeri 2 Pontianak. This research uses a descriptive qualitative method with a survey form. The subjects of this research is 35 students in class VIII F MTs Negeri 2 Pontianak. Data collection techniques that used were test and and non-test. Data collection tools that used were conceptual understanding tests and interview. The results of data analysis from this study indicate that the epistemological obstacle of students' mathematical conceptual understanding based on the SOLO taxonomy from 35 students is 40% of students are in level 0 (prestructural); 11.43% of students are in level 1 (unistructural); 20% of students are in level 2 (multistructural); 25.71% of students are in level 3 (relational); and 2.86% of students are in level 4 (extended abstract). The obstacle of students that have at level 0 are all of conceptual understanding indicator. Students at level 1 and 2 have obstacles in indicators 2, 3, and 4. Students at level 3 have obstacles in indicators 2 and 4. Students at level 4 have obstacles in indicator 4.Keywords: Epistemological obstacle, Mathematical Conceptual Understanding, SOLO Taxonomy